2014
DOI: 10.7314/apjcp.2014.15.12.4753
|View full text |Cite
|
Sign up to set email alerts
|

Biotoxins for Cancer Therapy

Abstract: In recent times, a number of studies have provided evidence that biotoxins present great potential as antitumor agents, such as snake venom, bee venom, some bacteria toxins and plant toxins, and thus could be used as chemotherapeutic agents against tumors. The biodiversity of venoms and toxins make them a unique source from which novel anticancer agent may be developed. Biotoxins, also known as natural toxins, include toxic substances produced by plants, animals and microorganisms. Here, we systematically list… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 50 publications
0
25
0
4
Order By: Relevance
“…Therefore, new treatments for various types of cancers, including cervical cancer [9, 10], are considered one of the greatest challenges to medicine today because of the resistance to the effects due to repeated exposure [11]. Interventions with the use of chemotherapy are far from satisfactory, because of side effects, destruction of healthy cells, and above all acquired resistance by tumors [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, new treatments for various types of cancers, including cervical cancer [9, 10], are considered one of the greatest challenges to medicine today because of the resistance to the effects due to repeated exposure [11]. Interventions with the use of chemotherapy are far from satisfactory, because of side effects, destruction of healthy cells, and above all acquired resistance by tumors [1214]. …”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome cDDP resistance and reduce normal cell toxicity, combination therapies of cDDP with other drugs, especially natural toxins have been highly considered. In the search for new cancer agents, biotoxins have recently attracted attention owing to their novel mode of actions and decreased possibility of resistance development (Gaspar et al 2013;Gajski et al 2014;Liu et al 2014). Bee venom (BV) has been used in oriental medicine as a source of drugs to cure different disorders (Son et al 2007;Oršolić 2012;Liu et al 2014;Premratanachai and Chanchao 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Liu et al4 and Calderon et al34 reported many anticancer bioactive molecules present in the snake venoms. In our study, we also observed cell disintegrity that was clearly observable due to severe distortion in colony formation and cell movement in the snake-venom-treated cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…The abundance of this enzyme is responsible for neuro- and cytotoxicities, edema, thrombocytopenia, and impairment of blood clotting factors 3. In addition, researchers have discovered the presence of l -amino acid oxidase and disintegrin in snake venoms that can damage cellular integrity 4. Interestingly, under proper pharmacological regulation, snake venoms can be beneficial in treating certain types of chronic diseases including cancer.…”
Section: Introductionmentioning
confidence: 99%